Need Analysis for Development ELT Material for the Islamic Education Management Department Students at UIN Alauddin Makassar - Ananda Amalia,; Kaharuddin, Kaharuddin; Asmawati, Andi (English Language Teaching for EFL Learners Journal, 2023)
This research investigated the need for English for Islamic Education Management Department students at UIN Alauddin Makassar. The researcher involved 44 respondents, 40 students, 1 lecturer, and 3 graduates in this study. A questionnaire and open-ended Questions were employed to collect the data. The findings show that the students' ability levels of all components of English (reading, writing, speaking, listening, grammar, and vocabulary) are at the 'adequate' level. The students prefer to study the components of English sequentially: (1) speaking average (3.44), (2) reading average (3.42), (3) listening average (3.42), (4) vocabulary average (3.42), (5) writing with an average (3.38), and (6) grammar with an average (2.77). The problem experienced by students in learning is a "Lack of learning English strategies," with the highest average score of (3.22). In addition, the most preferred learning method by students is Speaking, with an average score (3.33). The students were also interested in some of the most preferred learning styles, such as movies and videos, with an average score (3.31). The goals of this research are 1) to help students improve their English skills and 2) to help students have a good understanding of English language texts on topics of the Islamic Education Management course. It implies that the material that will be developed and provided by the result of the need analysis will fulfill the students.